’Listen: Still, the Echo of Loss’. Choctaw and Irish Transcultural Engagement in the Poetry of LeAnne Howe and Doireann Ní Ghríofa - Ní Éigeartaigh, Aoileann (TransCulturale, 2023)
This article discusses a sequence of poems in which Choctaw writer LeAnne Howe and Irish poet Doireann Ní Ghríofa “call and respond” to each other across history and space. It will suggest that through their willingness to listen, embrace of linguistic hybridity and determination to remain open to the nuances of history, the poems truly embody what Francine Rosenbaum describes as “transculture in narrative” (Rosenbaum 2018).